(untitled) (Práxis Educativa, 2024)
The teaching-learning process of Natural Sciences can be stimulated with neurofunctional aspects for cognitive development, through active innovative methodologies. Given this situation, the objective of the research was to train and educate teachers about Modeling Based Learning (MBL) and the use of Artificial Intelligence (AI), and to promote the design and implementation of neurodidactic sequences applicable in classrooms. Methodologically, the research was mixed where 35 teachers and 125 Elementary School students participated; a post-intervention instrument and a semi-structured interview were used. The results infer that the neuroeducational moments guided by the teachers generated significant learning and positive emotions in the students. It is concluded that interconnecting MBL and AI promotes decent and quality education, in accordance with the new global educational scenarios and favors the development of techno-scientific competencies. Keywords: Modeling Based Learning. Artificial Intelligence. Neuroeducation.